Learning Organization; Upaya Membangun Kapasitas Kepemimpinan Guru - Ima Rahmawati (Institut Agama Islam Sahid (INAIS) Bogor, 2021)
Teacher leadership and teacher development are key to building capacity for sustainable school improvement. Evidence shows the importance of teachers working together and learning together in generating the capacity for change. Building leadership capacity requires a constructivist learning approach in which teachers learn together and build meaning from professional interaction, discussion and dialogue. The birth of leaders at every level of leadership in schools through the building/development of teacher leadership capacities is a hallmark of effective leadership which ultimately gives birth to advanced and superior schools. Schools are organizations. As an organization, schools seek to improve their products, services, and innovations through